New onset episodic vertigo as a presentation of vestibular neuritis - Tang, Lu; Jiang, Weiwei; Wang, Xiaoshan (Frontiers in Neurology, 2022)
Objective: Vestibular neuritis (VN) is a common peripheral cause of acute vestibular syndrome, characterized by sustained vertigo or gait instability, persisting from one day to several weeks. With the widespread use of comprehensive vestibular function tests, patients with VN and non-sustained vertigo have drawn attention. In this study, we retrospectively analyzed the clinical presentation of patients with VN and paroxysmal vertigo, aiming to expand the atypical clinical features of VN. Methods: This retrospective study enrolled 57 patients with VN. Among them, 11 patients with symptomatic remission of more than 3 times per day for more than 1 hour each time were assigned to the paroxysmal vertigo (PV) group, and 46 subjects without significant relief into the sustained vertigo (SV) group. Demographic information, clinical manifestations and data of supplementary examinations were collected and statistically analyzed. These patients were followed up once a year to gather prognostic information. Results: The incidence of spontaneous nystagmus (SN) and proportion of severe vertigo (Dizziness Handicap Inventory questionnaire score ≥ 60) in the SV group were significantly higher than those in the PV group. Spearman correlation showed that with a longer disease course, the velocity of overt saccade was smaller (p < 0.05, Rs = - 0.212) in patients with VN. All the patients relieved from their symptoms after approximately two weeks of treatment. Conclusion: The non-sustained manifestations of VN may bring diagnostic confusion between VN and stroke-related vertigo. Our retrospective analysis of the clinical